Comparative Evaluation of Root Canal Transportation by Three NiTi Single-File Systems in Curved Canals: A Cone Beam Computed Tomography Study - Eshaghali Saberi; Narges Farhad-Mollashahi; Shima Bijari; Mohammad Daryaeian (Hindawi Limited, 2018)
Introduction. This study is aimed at evaluating root canal transportation in the mesiobuccal canal of mandibular first molars prepared with One Shape, Reciproc, and M-One nickel titanium (NiTi) single-file rotary systems using cone beam computed tomography (CBCT). Materials and Methods. In this ex vivo study, CBCT scans of 45 extracted human mandibular first molars with 20-40° curvature were obtained. The teeth were randomly divided into three groups (n=15) for preparation of the mesiobuccal canal with One Shape, Reciproc, and M-One rotary systems according to the manufacturers' instructions. CBCT scans were obtained again after canal preparation. Changes caused by preparation in the coronal, middle, and apical thirds were determined on CBCT scans and analyzed using the Kruskal-Wallis test at P≤0.05 level of significance. Results. No significant difference was noted in the amount of canal transportation among the three groups (P>0.05). M-One caused greater transportation in the apical third compared with Reciproc and One Shape, and One Shape caused greater transportation in the coronal third compared with other groups, although its magnitude was less than 0.3 mm. Conclusion. Reciproc, One Shape, and M-One are not significantly different in terms of canal transportation.